Characterization of coagulase-negative staphylococci by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and immunoblot analyses. - Thomson-Carter, F M (1989)
Coagulase-negative staphylococci are important nosocomial pathogens. At present, no wholly satisfactory typing scheme exists for these organisms. Therefore, sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and immunoblotting were assessed as characterization methods. A total of 100 type strains and nontyped isolates representing nine species of coagulase-negative staphylococci were analyzed. Each species had a reproducible, characteristic whole-cell banding pattern when analyzed by either method. These species-specific profiles were obtained for all isolates despite disparate geographical origins and clinical isolation sites. Intraspecies similarities, calculated by using the Dice coefficient, were significantly higher than interspecies similarities. Although some species were more heterogeneous than others, the allocation of isolates to any particular species was reinforced by the high degree of interspecies dissimilarity. Application of SDS-PAGE also distinguished discrete subspecies groups. These groups possessed the characteristic profile of their species but were distinguished by a group of variable polypeptides. Species-specific banding patterns were also obtained by immunoblotting of whole-cell polypeptides. Differences between immunoblot and SDS-PAGE profiles could be attributed to variations of antigenicity of particular polypeptides. However, both SDS-PAGE and immunoblotting provided reproducible and sensitive methods for characterization of coagulase-negative staphylococci. Standardization of these techniques could provide the basis for a primary typing scheme.